THE ROLE OF MOTIVATION IN MEDIATING PSYCHOLOGICAL DETERMINANTS OF EMPLOYEE PERFORMANCE - Eko Fauzan Adima; Muhammad Imam Muttaqijn; Dudung Hadiwijaya (Univesitas Muhammadiyah Tangerang, 2026)
This research is motivated by the importance of psychological factors, such as emotions and perceptions, in driving employee performance in public agencies, specifically at the Tangerang City Environmental Agency. The study aims to analyze the influence of emotions and perceptions on employee performance, both directly and indirectly through work motivation as a mediating variable. A quantitative approach with a survey method was employed. Data were collected through questionnaires distributed to 71 employees of the agency, supplemented by observation and documentation. The analysis utilized multiple linear regression and path analysis. The results indicate that emotions and perceptions significantly influence employee performance, both directly and indirectly via work motivation. The indirect effect was found to be greater than the direct effect, underscoring the key mediating role of motivation. These findings confirm that managing emotional and perceptual aspects can be an effective strategy for enhancing performance. The novelty of this research lies in testing the mediating role of work motivation in the relationship between emotions, perceptions, and performance within a public sector context. It offers a practical contribution by providing insights for designing human resource development strategies focused onÂ